Myasthenia gravis with double-seropositive acetylcholine receptor and low-density lipoprotein receptor-related protein 4 antibodies combined with muscle atrophy: a case report and literature review - Zheng, Yue-liang; Su, Gong-zhang; Li, Yan-lin; Du, Tong; Zhao, Xue-lu; Wang, Cong-cong; Liu, Ying; Liu, Bin; Duan, Rui-sheng; Li, Xiao-li (Frontiers in Immunology, 2025)
ObjectiveTo investigate the clinical characteristics and mechanisms of muscle atrophy in myasthenia gravis (MG) patients who are double-seropositive with acetylcholine receptor (AChR) antibodies and low-density lipoprotein receptor-related protein 4 (LRP4) antibodies.MethodsThe clinical data, imaging characteristics, treatment methods, and prognosis of one case of MG with AChR/LRP4 antibodies complicated by muscle atrophy were analyzed. Literature on anti-AChR/LRP4 antibodies double-seropositive MG with muscle atrophy were reviewed.ConclusionClinically, anti-AChR/LRP4 antibodies double-seropositive MG is rare, often onset after middle age, more common in females, frequently involving bulbar muscles, severe symptoms, poor prognosis, and unrelated to thymoma. Muscle atrophy in MG is not only seen in muscle-specific tyrosine kinase (MuSK)-MG but also in AChR-MG and seronegative MG. The mechanism of muscle atrophy may be related to genetic, immune, and nutritional factors.